Elections and democratization in the Middle East the tenacious search for freedom, justice, and dignity - Hamad, Mahmoud; al-Anani, Khalil; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Top scholars of the Middle East set out the history and future of elections in eight Middle East countries. Examining issues associated with elections, the transition of governance, and the ways in which technology shapes popular participation in politics and elections, they discuss the future of governance and democratic transition in the region.
Keywords: Political science; Democracy; Elections; Middle East -- Politics and government; Political Science and International Relations; Electoral Politics; Middle Eastern Politics; Political Science; Democracy